Pengaruh Kepribadian, Lingkungan Keluarga Dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Pada Siswa Kelas X OTKP SMKN 2 Cikarang Barat - Kazeka Prianto, Wahyu; Yohana, Corry; Fadillah, Nadya (Rifa'Institute, 2023)
This research is motivated by the low interest in entrepreneurship among class X students of SMKN 2 Cikarang Barat. This study aims to determine the influence of personality, family environment and entrepreneurship education on interest in entrepreneurship in class X students of SMKN 2 Cikarang Barat. This study used a survey method with a questionnaire as a data collection instrument. The collected data were analyzed using tools in the statistical application program, namely Statistical Product and Service Solutions (SPSS). The population consisted of 112 students from class X SMKN 2 Cikarang Barat. In this study, it was found that personality, family environment and entrepreneurship education had a positive and significant effect on interest in entrepreneurship in class X students of SMKN 2 Cikarang Barat.